2013
DOI: 10.1038/bjc.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Low penetrance susceptibility to glioma is caused by the TP53 variant rs78378222

Abstract: Background:Most of the heritable risk of glioma is presently unaccounted for by mutations in known genes. In addition to rare inactivating germline mutations in TP53 causing glioma in the context of the Li-Fraumeni syndrome, polymorphic variation in TP53 may also contribute to the risk of developing glioma.Methods:To comprehensively evaluate the impact of variation in TP53 on risk, we analysed 23 tagSNPs and imputed 2377 unobserved genotypes in four series totaling 4147 glioma cases and 7435 controls.Results:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 28 publications
2
45
0
1
Order By: Relevance
“…The association with glioma was confirmed in an independent European study (32). To refine the association signal at 8q24.21 in glioma, the region was fine-mapped by sequencing as well as statistical imputation of preexisting GWAS datasets.…”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 58%
See 1 more Smart Citation
“…The association with glioma was confirmed in an independent European study (32). To refine the association signal at 8q24.21 in glioma, the region was fine-mapped by sequencing as well as statistical imputation of preexisting GWAS datasets.…”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 58%
“…27). A number of additional studies have replicated the association between rs78378222 and glioma risk (20, 32, 113, 114). …”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 92%
“…Similarly, the lack of a positive confirmation of associations between rs2736100 (5p15.33; TERT) and both glioma overall (P ¼ 0.0655) and GBM (P ¼ 0.0788) is likely attributable to small sample sizes, especially when factoring in previous results indicating an association between rs2736100 and glioma risk among incident cohort cases (11). Furthermore, the 17p13.1 (TP53) variant rs78378222 has previously been associated with risk for both GBM and non-GBM tumors (31). In this study, we found an association with risk for glioma overall (i.e., all glioma diagnoses, not including ependymoma), but it did not replicate specifically for GBM (P ¼ 0.1012).…”
Section: Discussionmentioning
confidence: 83%
“…To date, TP53 database of the International Agency for Research on Cancer (IARC) collected several hundred pedigrees having Li-Fraumeni/Li-Fraumenilike syndromes, with the genetic status of germline TP53 mutations (8,16). We also found that a large number of publications was dealing with cancer patients with the germline TP53 mutations showing no typical features of Li-Fraumeni/Li-Fraumeni-like syndromes; a part of these cases could be explained by the low penetrance of the germline TP53 mutations (2,23) . We investigated the germline TP53 variations in cancer patients belonging to the Project HOPE cohort through several steps.…”
mentioning
confidence: 91%